The nature of a house : - Woodwell, George M. (Island Press, 2009)
The Nature of a House is a candid, charming, and illuminating book. Woodwell tells a story that will interest anyone who has ever thought about doing a 'green' rehab, has tried to build green, or just wonders what is actually possible.